Adaptive micro strip antennas for 5G networks - Lakshmi Narayana Sudha, Kanakatte; Pallipadi Jayaprakash, Sapna; Neralahalli Prakash, Deepa (Institute of Advanced Engineering and Science, 2025)
The advent of fifth-generation (5G) technology and progressing further to six-generation (6G) technology has created a new era of high-speed wireless communication, demanding antennas with enhanced capabilities to fulfill the dynamic demands of various applications. This paper presents novel approaches to designing antennas in the GHz frequency range for 5G networks by incorporating re-configurability features. Adaptive antennas provide the flexibility to alter their radiation configurations, frequencies, or polarization states, allowing them to optimize performance under different operating conditions. The theoretical foundations are explored, and reconfigurable antennas are simulated using HFSS, focusing on frequency and pattern variation at GHz frequencies using different types of switches such as pin diodes and rods. Through simulations, the antenna's S parameters are evaluated, demonstrating its capacity to meet the rigorous specifications of 5G applications. Its adaptive nature enhances connectivity and overall network performance, supporting the successful deployment and advancement of 5G technology in diverse real-world applications.